sFlt-1/PlGF Ratio for the Predictive Diagnosis of Preeclampsia: Budget Impact Analysis from the Public Healthcare Perspective in Portugal - Campos, A (2019)
Overview and Aims: The last decade brought relevant insights into the pathophysiology of preeclampsia (PE), namely the role of the circulating levels of placental growth factor (PlGF) and soluble Fms-like tyrosine kinase-1 (sFlt-1). The purpose of this study is to estimate the financial impact of introducing the sFlt-1/PlGF ratio for the evaluation of women with suspicion of PE in the Portuguese National Healthcare System (SNS). Study Design: budget impact study evaluating short-term costs associated with the introduction of the sFlt-1/PlGF ratio from the SNS payer’s perspective. The time horizon for the study is 1 year. Population: The target population consists of women presenting to the healthcare system with signs or symptoms su ggestive of preeclampsia (estimated in 8500 subjects). Methods: A decision-tree model was used to estimate the budget impact of the introduction of the sFlt-1/PlGF ratio in the SNS. The model compares the management costs in the current clinical practice (“no test” scenario) vs. current diagnostic procedures plus the sFlt-1/PlGF ratio (“test” scenario). Clinical inputs have been derived primarily from literature review and, where data was unavailable, expert opinion. Resources and unit costs have been obtained from Portugal-specific sources. Results: In the current standard practice (no test), total costs were estimated to be €9 863 264 (€1160 per patient), with unnecessary admissions representing about €3,5 million. Total costs in the test scenario sum up to €9 781 194 (€1150 per patient), representing a cost saving to the system of €82 070 (€10 per patient), mainly due to a reduction of false positives and related unnecessary hospitalizations of women not developing PE. Conclusions: There is favorable economic evidence about the introduction of the sFlt- 1/PlGF ratio in the SNS. The generated savings appear to offset the costs related to the test.